可降解医用弹簧圈 (2018)
本发明提供了种可降解医用弹簧圈。该可降解医用弹簧圈包括：裸金属弹簧圈本体，其由镁或者镁合金材料制备。本发明克服了技术偏见，将镁或镁合金作为生物可降解材料应用到医用弹簧圈中，由于镁元素是维持人体正常新陈代谢的过程中不可或缺的元素，医用弹簧圈在降解后的元素可为人体所利用，并可由肾脏和小肠保持其浓度稳定，同时，安全期后会完全降解，没有残留物，避免了占位效应，不会产生金属伪影进而影响后期的影像学随访，具有较强的使用价值。 The invention provides a degradable medical spring ring, which comprises a bare metal spring ring body, wherein the bare metal spring ring body is prepared from magnesium or magnesium alloy materials. The technical defects are overcome. The magnesium or magnesium alloy is used as a biodegradable material to be applied to a medical spring ring. The magnesium element is an indispensable element in the process of maintaining the normal metabolism process of the human body; the elements of the medical spring ring after the degradation can be used by the human body; the stable concentration of the elements can be maintained by the kidney and the small intestines; meanwhile, the elements can be completely degraded after the safe period; no residue is left; the space occupying effect is avoided; the influence o